The leishmanicidal activity of essential oils: A systematic review - Shamsi Noorpisheh Ghadimi; Negin Sharifi; Mahmoud Osanloo (Shahrekord University of Medical Sciences, 2020)
Leishmaniasis is the neglected disease among parasitic diseases with an increasing rate of infections. Recently, numerous studies have been conducted on the leishmanicidal properties of various essential oils (EOs). In this research, literature have been systematically reviewed, from 20 years ago, and required information have been extracted. Overally, leishmanicidal effects of ~180 EOs against promastigotes of nine species of Leishmania havebeen documented. Inhibitory concentrations 50% (IC50) of around 30 EOs were less than 10 μg.mL-1. EOs of Tetradenia riparia, Nectandra hihua, and Thymus hirtus with IC50s of 0.01,0.20, and 0.25 μg.mL-1 against Leishmania amazonensis, Leishmania infantum, and Leishmania major respectively, were identified as the most effective EOs. Furthermore, IC50 of Thymus hirtus on Leishmania infantum was 0.43 μg.mL-1. Frequently, substantial differences were found between the observed IC50s of one EO against promastigotes of different species of Leishmania. It can be concluded that the leishmanicidal activity of EOs is selective. Turning to the results,the combination of EOs for the design of multifunctional drugs can lead to excellent outcomes.Interestingly, the results have been classified by promastigote species, so this would be a valuablebenchmark for researchers.